Ekonomiczne i prawne aspekty podziału władztwa podatkowego między państwo i władze lokalne - Walasik, Artur (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The aim of the paper is to present and discuss theoretical approaches to the problem of distribution of limited power to taxation between state and local authorities. Four basic models are reviewed: tax competition model and tax separating model as well as tax participation model and tax supplement model. Both legal and economic consequences of implementing each of presented models are discussed. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 208-219